NEUROMUSCULAR RESPONSES OF THE HAMSTRING MUSCLES DURING UNANTICIPATED TRUNK PERTURBATIONS. Issue 4 (1st February 2017) - Higashihara, Ayako; Nagano, Yasuharu; Ida, Hirofumi; Nakazawa, Kimitaka
Abstract : Background: Anterior cruciate ligament and hamstring strain injuries occur during unanticipated cutting and stopping movements. Previous prospective studies showed that athletes with decreased trunk neuromuscular control are at increased risk of knee injury. Therefore, deficits in trunk neuromuscular control during unanticipated movements may result in injury. However, the modulations of the hamstring muscles to the unanticipated trunk perturbation are unclear. Objective: To examine the neuromuscular responses of the hamstring muscles during unanticipated trunk perturbations. Design: Descriptive laboratory study. Setting: Male college athletes. Participants: Eight male sprinters (age, 20.3±1.4 years). Intervention: In the kneeling position, the participants wore a chest harness attached to a cable that was pulled backward as a resisting force at a constant level corresponding to 13% to 15% of each weight. The participants were instructed to resist the force isometrically. The force was released with cue (CUE) and without cue (NoCUE). Trunk acceleration and surface electromyography (EMG) signals of the erector spinae, gluteus maximus, biceps femoris, and semitendinosus muscles were measured. Main Outcome Measurements: (1) Maximum trunk acceleration; (2) EMG activation in the 50-ms window before the perturbation; (3) onset time of the muscle response; and (4) phasic muscle activities after the perturbations. Results: The maximum trunk acceleration was significantly greater during the NoCUE condition than during the CUE condition ( p <0.01). No significant differences were observed in either of the EMG activations before the perturbation. The activation onsets of the hamstring muscles were significantly delayed ( p <0.05) and the activation responses of these muscles from 100 ms after the perturbation were significantly larger during the NoCUE than during the CUE condition ( p <0.05). Conclusions: The results indicate that the anticipation of perturbation decreased the hamstring muscle latencies and responses to control the trunk movement, suggesting that the central nervous system modulated the readiness of the trunk based on anticipatory information.